Unraveling Turnover Dynamics: The Strategic Role of Employee Engagement and Career Pathways - Damayanti, Tri; Maryadi, Adi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This research offers a comprehensive exploration of the relationship between employee engagement, career management, and employee turnover within organizational environments. Utilizing a quantitative approach, data were gathered through structured surveys involving participants from various professional backgrounds. The analysis reveals that career management has a significant and positive impact on employee turnover, highlighting the importance of robust career development initiatives in retaining valuable talent. Furthermore, employee engagement was found to significantly influence career management practices, emphasizing its essential role in encouraging employees to take ownership of their professional development. However, the study identified no direct and significant relationship between employee engagement and turnover, suggesting that while engagement can foster motivation and positive work behaviors, it may not be sufficient to reduce turnover unless supported by tangible opportunities for career progression. This underscores the need for organizations to adopt a more integrated human resource strategy—one that combines engagement efforts with structured, transparent, and supportive career development frameworks. For HR practitioners and organizational leaders, these findings offer critical insights. Strengthening career management systems—such as implementing clear advancement pathways, customized development plans, and consistent training programs—can effectively reduce employee turnover, reinforce organizational commitment, and cultivate long-term workforce loyalty. Ultimately, the study advocates for a holistic approach to employee retention, where individual aspirations are aligned with the organization’s strategic vision, fostering sustainable growth and employee satisfaction over time.